Evaluasi Hasil Pelatihan di Pusdiklat Tenaga Teknis Pendidikan dan Keagamaan - Ratna Prilianti; Ma'arif; Gunarno (Andragogi: Jurnal Diklat Teknis Pendidikan dan Keagamaan, 2020)
[THE EVALUATION OF TRAINING RESULTS IN THE EDUCATION AND RELIGIOUS TECHNICAL TRAINING CENTER]. The purpose of this study is to analyze the training results which are focused on the satisfaction of training alumni with education services in the Education and Religious Technical Training Center of the Ministry of Religion. This research is survey research to stakeholders in the Province of North Sumatra, Central Java, D.I. Yogyakarta and South Sulawesi with sampling were done with a purposive random sampling technique with a total of 50 people. The instruments used are questionnaires, interview guidelines, and document checklist. While the data analysis is done by editing, tabulating, and IKM analyzing as well as interpretations. The results of this study indicate that in the alumni satisfaction index of education and training services at that the quality category of service elements, namely: 1) Requirement Elements get 84 (B/Good category); 2) System, mechanism, and procedure elements get 87,5 (B/Good category); 3) The completion time element gets 86 (B/Good category); 4) The cost/tariff element gets 94,625 (category A/Very Good); 5) The product element specification type of service gets 85 (category B/Good); 6) The element of implementing competency gets 88,063 (category B/Good); 7) The element of implementing behavior gets 88.5 (category A/Very Good); 8) The element of complaint handling, suggestions, and input get 77.5 (category B/Good); and 9) The elements of facilities and infrastructure get 83,929 (category B/Good). The results of the average conversion value obtained results of 85.26 which based on the index is in the "B" or "GOOD" category.